Standard practice for testing chromate coatings on zinc and cadmium surfaces
This standard is issued under the fixed designation B201; the number immediately following the designation indicates the year of original adoption or, in the case of revision, the year of last revision.This practice covers a procedure for evaluating the protective value of chemical and electrochemical conversion coatings produced by chromate treatments of zinc and cadmium surfaces.